Nursery Evaluation of Promising Species/Varieties of Leucaena for Fast Growth under Mid-hill Conditions of Himachal Pradesh - Chauhan, K. C.; Hasolli, R. (Indian Forester, 2004)
Forty nine species/varieties of Leucaena were procured from different sources within and outside the country with an objective to screen the best species/varieties under nursery condition for the suitability under mid-hill conditions of Himachal Pradesh. The analysis of variance revealed highly significant differences among different species/varieties for seedling growth and biomass traits. After five months nursery growth T38 (Leucaena esculenta × esculenta , ID-47/87) and T37 (L. esculenta × paniculata , ID-79/92) excelled for growth and biomass traits than others , whereas , T1 (L. pulverulenta × L. leucocephala-K75) depicted the least values for collar diameter , inter nodallengtb , leaf area , root fresh and dry weight , T44 (L. multicapitulata , ID-81/87) for seedling height and number of nodes , T4 (L. pulverulenta , ID- 84/87) and T21 (L. diversifolia , ID-45/87) for shoot fresh and dry weight.